Social abilities and the use of virtual social media of students of senior secondary grade in private and public schools in Metropolitan Lima - Delgado Vásquez, Ana Esther (2020)
DOI: 10.26439/persona2020.n023(1).4831 This research studies the interaction between social habilities and activity on internet social networks in fifth grade high school students of the town of Lima. The participants were 1066 students and the sample was a probabilistics one. We used a correlational design, as it was sought to determine the degree of relationship between two variables, in this case the index of relation between social habilities and the index of use of internet social networks in high school participants from a state and a non state institutions of the city of Lima. Results show a negative and significant interaction between the full score on the scale of social skills and the index of addiction to internet networks, as well as in the scores of most of the components of the results of the variables under study.